IMPLEMENTASI PENDIDIKAN MULTIKULTURAL (Studi Kasus di SD Negeri Rejoagung 2 Jombang) - Choirul Anam; Tuti Marlina (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Indonesia is a country that has a variety of diversity. This plurality sometimes triggers the emergence of various problems related to the existence of social, ethnic and religious groups. Multicultural education can be a solution to the problem of diversity. The objectives of this study are: (1) To determine the implementation of multicultural education in student teaching and learning activities (2) To determine the evaluation of the application of multicultural education. This study uses qualitative research methods using verbal data, so that it uses observation and unstructured interview technique that is theoretical. The results of this study indicate that (1) the implementation of multicultural education is oriented towards activities carried out in groups or together. These activities are intended so that students develop into tolerant individuals so that they are able to get along with anyone without discriminating. (2) Evaluation of multicultural education is carried out during the learning process which is called process evaluation and final evaluation, which is called outcome evaluation. The evaluation is adjusted to the indicators of multicultural education that have been listed in the lesson plans.